PGR5-PGRL1-Dependent Cyclic Electron Transport Modulates Linear Electron Transport Rate in Arabidopsis thaliana - Suorsa, Marjaana; Rossi, Fabio; Tadini, Luca; Labs, Mathias; Colombo, Monica; Jahns, Peter; Kater, Martin M.; Leister, Dario; Finazzi, Giovanni; Aro, Eva-Mari; Barbato, Roberto; Pesaresi, Paolo (Molecular plant, 2016)
Plants need tight regulation of photosynthetic electron transport for survival and growth under environ- mental and metabolic conditions. For this purpose, the linear electron transport （LET） pathway is supple- mented by a number of alternative electron transfer pathways and valves. In Arabidopsis, cyclic electron transport （CET） around photosystem I （PSI）, which recycles electrons from ferrodoxin to plastoquinone, is the most investigated alternative route. However, the interdependence of LET and CET and the relative importance of CET remain unclear, largely due to the difficulties in precise assessment of the contribution of CET in the presence of LET, which dominates electron flow under physiological conditions. We there- fore generated Arabidopsis mutants with a minimal water-splitting activity, and thus a low rate of LET, by combining knockout mutations in Psb01, PsbP2, PsbQ1, PsbQ2, and PsbR loci. The resulting 45 mutant is viable, although mature leaves contain only ~20% of wild-type naturally less abundant Psb02 protein. 45 plants compensate for the reduction in LET by increasing the rate of CET, and inducing a strong non-photochemical quenching （NPQ） response during dark-to-light transitions. To identify the molecular origin of such a high-capacity CET, we constructed three sextuple mutants lacking the qE component of NPQ （45 npq4-1）, NDH-mediated CET （45 crr4-3）, or PGR5-PGRLl-mediated CET （45 pgrS）. Their analysis revealed that PGR5-PGRLl-mediated CET plays a major role in ~pH formation and induction of NPQ in C3 plants. Moreover, while pgr5 dies at the seedling stage under fluctuating light conditions, 45 pgr5 plants are able to survive, which underlines the importance of PGR5 in modulating the intersystem electron transfer.